Melatonin protects against pancreaticobiliary inflammation and associated remote organ injury in rats: role of neutrophils - (:unkn) unknown (WILEY, 2004)
Although the role of oxidative stress in acute pancreatitis (AP) has been studied in several animal models, little data are available regarding AP induced by pancreatic duct obstruction. We characterized the protective effects of melatonin on pancreaticobiliary inflammation and associated remote organ injury. In Sprague-Dawley rats, either the common pancreaticobiliary duct (PBDL; n = 28) or bile duct (BDL; n = 28) was ligated or a sham operation was applied (n = 14). Either melatonin (10 mg/kg) or vehicle (saline; 1 mL/kg) was administered intraperitoneally (i.p.) immediately before the surgery and twice a day until the rats were decapitated at 6 or 72 h. The pancreas, liver, kidneys and lungs were removed and tissue samples were stored for the determination of malondialdehyde (MDA) and glutathione (GSH) levels and myelopreoxidase activity. The results demonstrate that pathogenesis of acute obstructive pancreatitis involves not only the oxidative damage of the pancreatic and hepatic tissues, as assessed by increased MDA and reduced GSH levels, but the lungs and kidneys are also challenged by oxidant injury. Similarly, hepatic oxidative injury caused by cholestasis was also accompanied by pulmonary, renal and even pancreatic damage. The biochemical findings were also verified histologically. Melatonin, probably because of its free-radical scavenging and antioxidant activity, which involves an inhibitory effect on tissue neutrophil infiltration, protected all the affected tissues.
Keywords: acute obstructive pancreatitis; antioxidants; cholestatic liver injury; melatonin; myeloperoxidase activity; oxidative stress; INDUCED ACUTE-PANCREATITIS; OXIDATIVE STRESS; LIPID-PEROXIDATION; FREE-RADICALS; ZYMOGEN ACTIVATION; DUCT OBSTRUCTION; ACINAR-CELLS; GLUTATHIONE; OXYGEN; BILE